Reference values for Down’s cephalometric analysis in Papuans - Shella Indri Novianty; Budi Suhartono (Majalah Kedokteran Gigi Indonesia, 2021)
The asessment of cranio-facial structures forms a part of orthodontic diagnosis and treatment. One of the most frequently used cephalometric analysis is the Down’s analysis. It consists of 10 parameters of which 5 are skeletal and 5 are dental. Down has based his findings on 20 Caucasians, which have physical characteristic differences with Papuans. Indigenous Papuans are people of Melanesian descent consisting of indigenous tribes in Papua province and/or people who are accepted and recognized as Papuans by indigenous Papuans.The use of cephalometric values in different racial types, may result in the incorrect orthodontic diagnosis and treatment plan. According to those, the objectives of this study are to determine reference values for Down’s cephalometric analysis in papuans, to evaluate the differences exists between Papuan adult male and female, and also to compare the mean difference between persent study and established value of Down’s norms. A study was conducted on 16 lateral cephalograms of Papuans that have been selected based on inclusion criteria. The Down’s method was used for the cephalometric analysis. The data obtained was processed statistically to determine the mean, standart deviation, and minimum-maximum value, and presented in the form of frequency, table, or diagram. The result showed that the normal cephalometric values of papuans different from the normal values used in the Down’s analysis. The values obtained in this research is expected to be a reference in conducting Down’s cepahlometric analysis in Papuans for orthodontic treatment purposes.